Longitudinal Examination of Victimization Experiences of Latinos (LEVEL): Extending the Bias Victimization Study, San Diego, CA, Galveston, TX, Houston, TX, Boston, MA, 2019-2020 - Cuevas, Carlos A. ([Verlag nicht ermittelbar], 2023)
The Longitudinal Examination of Victimization Experiences of Latinos (LEVEL) study surveyed Latino adults from four major cities across the United States to evaluate the past-year incidence and prevalence of bias or hate motivated victimization. This study is a follow-up to the Understanding and Measuring Bias Victimization Against Latinos study, ICPSR 37598, that was conducted in 2018-2019. The hope of this follow-up study, in conjunction with the original study "Wave 1", is to provide greater context into bias victimization by breaking apart the diverse nature of Latinx communities in regards to immigration status, language use, origin, acculturation, and enculturation.